PERANCANGAN SISTEM INFORMASI RAWAT JALAN PADA PRAKTEK DOKTER HERLINA - Ahmad Soleh; Winanti . (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2013)
AbstrakDESIGN ANALYSIS INFORMATION SYSTEM IN OUTPATIENT PRACTICE PHYSICIAN Herlina.Herlina Practice Physicians is an organization engaged in health. Herlina Physician Practice located in Kampung kawaron excited Rt 07 Rw 04, the Village Wanakerta Sindang Jaya District. In this Herlina Physician Practice outpatient process is needed due to replace the manual system, the data stored on these systems have not been well integrated and common mistakes in recording, so the process of outpatient services that are not in accordance with the procedure. With these problems it will be an outpatient information system designed to use the Access database and Visual Basic 2008. The data was collected using field research by interviewing directly to the relevant parties. This research aims to help companies improve the effectiveness of work and better data processing, for processing the data with the computerized system will provide fast and accurate data and to improve the efficiency and in the work process, but it can assist management in making decisions. The increasing number of patients and the data to be inputted, it needed a system that can produce a fast and accurate information so that the mechanism can be well controlled process. To solve the problem, so in this case the author makes the program using Visual Studio 2008 (Visual Basic.Net). with Access as the database and Crystal Report as a form of report. After the implementation of the system that the authors propose is expected to assist staff in inputting data. Because the new system each enrolled patient data can be well controlled.Key Words : DESIGN, ANALYSIS, INFORMATION SYSTEM, OUTPATIENT PRACTICE PHYSICIAN